Intercommunalite Et Amenagement Du Territoire Dans Le Departement De L'atacora Au Nord Ouest Du Benin - Yasmine Koladé Agnikè Ali Idrissou; Toussaint Vigninou; Benoît Nbessa (European Scientific Journal, ESJ, 2018)
Despite the 2009-17 law of 13th August 2009 which lay down that the Public Institution of Intercommunity Cooperation (EPCI) is the only form of intercommunality body in Bénin, municipal groupings still exist in associative form. This article analyses the impact of intercommunity cooperation on territory planning in the Department of Atacora. Data and information used have been obtained essentially through literature search and interviews of 47 resource persons concerned by the topic. Statistical and mapping tools have been involved for data processing. All in all, five (5) EPCI are regularly set up in Bénin and the Community of 2KP regrouping three (3) municipalities of the Department of Atacora is the first set up.. Like other EPCI, the 2KP Community face several constraints in the implementation of the intercommunality in the land use planning. Various solutions approach have been suggested to address those legal, institutional, financial, technical difficulties. Furthermore, the coexistence of EPCI with municipalities associations that have capitalized years of experience of intercommunity cooperation seems possible provided that they remove public works projects from their wallet activities.